Capturing the South : imagining America's most documented region - Matthews, Scott L. (Documentary arts and culture., 2018)
"In his expansive history of documentary work in the South during the twentieth-century, Scott L. Matthews examines the motivations and methodologies of several pivotal documentarians, including sociologist Howard Odum, photographers Jack Delano and Danny Lyon, and music ethnographer John Cohen. Their work salvaged and celebrated folk cultures threatened by modernization or strived to reveal and reform problems linked to [the] region's racial caste system and exploitative agricultural economy"--